Employment dynamics and business relocation: new evidence from the national establishment time series - David Neumark; Junfu Zhang; Brandon Wall (Institute for the Study of Labor (IZA), 2005)
We analyze and assess new evidence on employment dynamics from a new data source the National Establishment Time Series (NETS). The NETS offers advantages over existing data sources for studying employment dynamics, including tracking business establishment relocations that can contribute to job creation or destruction on a regional level. Our primary purpose in this paper is to assess the reliability of the NETS data along a number of dimensions, and we conclude that it is a reliable data source although not without limitations. We also illustrate the usefulness of the NETS data by reporting, for California, a full decomposition of employment change into its six constituent processes, including job creation and destruction stemming from business relocation, which has figured prominently in policy debates but on which there has been no systematic evidence.
Keywords: J2; C8; L0; 330; job creation; job destruction; employment dynamics; business relocation